Pengurusan Inventori Optimum dengan Menggunakan Aplikasi Model Kuantiti Pesanan Ekonomi (EOQ) : Kajian Kes di Batu Pahat - Mohd Lazim, Nur Nadia; R. Chandrashekar; Shafi, Muhammad Ammar (Research in Management of Technology and Business, 2020)
Inventory management is the practice of planning, directing and controlling inventory to contribute to business profits. Economic Order Quantity (EOQ) is a mathematical model for determining order quantities to reduce the cost of the order and the holding of the inventory. The purpose of this study was to identify the level of knowledge and application usage in the inventory management system using qualitative design. Where the interview method was made with a respondent in the company responsible for inventory management. And the past data obtained from the company will be analyzed using the EOQ Model to calculate the optimal quantity of inventory management and the total cost of inventory management in the company. This case study shows the optimum level of company’s inventory management and the results of the EOQ Model to calculate the quality and cost of optimum inventory management.